2016
DOI: 10.1016/j.celrep.2016.05.096
|View full text |Cite
|
Sign up to set email alerts
|

NeuCode Proteomics Reveals Bap1 Regulation of Metabolism

Abstract: SUMMARY We introduce neutron-encoded (NeuCode) amino acid labeling of mice as a strategy for multiplexed proteomic analysis in vivo. Using NeuCode we characterize an inducible knock-out mouse model of Bap1, a tumor suppressor and deubiquitinase whose in vivo roles outside of cancer are not well established. NeuCode proteomics revealed altered metabolic pathways following Bap1 deletion, including profound elevation of cholesterol biosynthetic machinery coincident with reduced expression of gluconeogenic and lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 65 publications
0
60
0
Order By: Relevance
“…Quantitative proteomic analysis of tissues from inducible Bap1 KO mice revealed a role in metabolic homeostasis in the pancreas and liver (55). Elevated cholesterol biosynthesis but reduced expression of gluconeogenic and lipid homeostasis proteins were observed in the liver.…”
Section: Lessons From Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative proteomic analysis of tissues from inducible Bap1 KO mice revealed a role in metabolic homeostasis in the pancreas and liver (55). Elevated cholesterol biosynthesis but reduced expression of gluconeogenic and lipid homeostasis proteins were observed in the liver.…”
Section: Lessons From Mouse Modelsmentioning
confidence: 99%
“…In the pancreas, expression of pancreatitis protein markers was increased whereas expression of mitochondria proteins was decreased. These mice also exhibited hypercholesterolemia, hypoglycemia, lipid reduction in the liver, and pancreatic acinar cell degeneration (55). How such metabolic dysregulation is related to cancer predisposition or tumorigenesis is yet to be determined.…”
Section: Lessons From Mouse Modelsmentioning
confidence: 99%
“…Because incorporation rates differ by tissue, it is important to confirm sufficient incorporation time for the tissue of interest. We found that incorporation of isotopologue into liver is faster than into brain or muscle and that 2 weeks of isotopologue incorporation would be sufficient for studying the liver while 4 weeks of incorporation is needed for studying brain or muscle 21 . Experimental models where growth or protein synthesis is severely affected are likely not good candidates for NeuCode labeling approaches for quantitation of relative protein abundance.…”
Section: Applications Of Neucode Silacmentioning
confidence: 88%
“…Since 2013, NeuCode SILAC has been applied to a number of different experimental models including yeast 4,11 , adherent cell lines 19 , nematodes 20 , and mice 21 . In this protocol we highlight the use of NeuCode for adherent cell lines and mouse models; however, application of the method to other model systems is straight forward and simply requires the dietary replacement of normal lysine with NeuCode lysine isotopologues.…”
Section: Applications Of Neucode Silacmentioning
confidence: 99%
See 1 more Smart Citation